(untitled) (International Journal of Physiotherapy, 2017)
Background: Sacroiliac joint dysfunction represents 15% of low back pain conditions. Normal sacroiliac joint works as a safeguard and transmits upper body weight into the pelvis and lower extremities. If the SIJ is hypomobile, it cannot effectively absorb forces and other body parts may be overstressed causing musculoskeletal dysfunction. The study conducted by comparing the effectiveness of Mulligan mobilization versus muscle energy technique in chronic SIJ dysfunction. Methods: 45 patients with chronic sacroiliac joint dysfunction from both genders joined the study. They were divided into three groups 15 in each group. Group A: received Mulligan mobilization with movement using posterior and anterior innominate methods plus conventional treatment program. Group B: received muscle energy technique using a post-isometric relaxation technique to erector spinae, hamstrings, iliopsoas and quadratus lumborum plus conventional treatment program. Group C: control group obtained conventional treatment program only. Doppler imaging of vibration, palpation meter, and the visual analogue scale was utilized for evaluating patients (pre and post-treatment). Results: The study findings revealed a statistical remarkable improvement in post-intervention values for sacroiliac mobility in Mulligan mobilization group (p > 0.0001) and a statistically significant decrease of anterior pelvic tilting angle in Mulligan mobilization and muscle energy technique groups (p > 0.0001), also a significant decrease of pain in the 3 groups compared with pre-intervention values (p > 0.0001), additionally, Mulligan mobilization group showed a statistical high detectable difference in right and left sacroiliac mobility more than muscle energy technique and control groups (p > 0.0001). Conclusion: Mulligan mobilization is more effective than muscle energy technique in the treatment of chronic sacroiliac joint dysfunction.